SISTEM PENGENALAN WAJAH 3-D MENGGUNAKAN PENAMBAHAN GARIS CIRI PADA METODE PERHITUNGAN JARAK TERPENDEK DALAM RUANG EIGEN - Lina, Lina; Kusumoputro, Benyamin (Makara Journal of Science, 2003)
3-D Face Recognition System using Additional Feature Lines in Nearest Feature Line Method in Eigenspace Representation. In this paper, the authors propose a new method in 3-D face recognition system using additional feature lines in Nearest Feature Line method, called the Modified Nearest Feature Line method. The additional feature lines can be acquired by projecting each feature point to other feature lines in the same class without increasing the number of feature points. With these additional lines, the system will have the ability to capture more variations of face images, so it can increase the recognition rate of the system. The authors also propose KL-TSubspace1 and KL-TSubspace2 as methods in transforming the 3-D face images from its spatial domain to their eigenspace domain. The experiments use the 3-D human faces of Indonesian people in various expressions and positions. Then, the system is applied to recognize unknown face images with different viewpoints. Experimental results shown that the system using KL-TSubspace2 and Modified Nearest Feature Line method can have the highest recognition rate of 99.17%.